Calorimetry-based profiling of blood plasma from colorectal cancer patients - Todinova, Svetla; Krumova, Sashka; Kurtev, Panayot; Dimitrov, Valentin; Djongov, Lachezar; Dudunkov, Zlate; Taneva, Stefka G. (Biochimica et biophysica acta, 2012)
Differential scanning calorimetry (DSC), a highly sensitive technique for resolving thermally-induced protein folding/unfolding transitions, recently was recognized as a novel tool for disease diagnosis and monitoring. To further elaborate this approach we have applied DSC in a study of blood plasma from patients with colorectal cancer (CRC) at different stages of tumor development and localization. Blood plasma from patients diagnosed with CRC was analyzed by DSC. The CRC thermograms were compared to those of healthy individuals and patients with gastric cancer and non-cancerous soft tissue inflammation. The thermodynamic parameters: excess heat capacity and enthalpy of the transitions corresponding to the most abundant plasma proteins, as well as transition and first moment temperatures were determined from the calorimetric profiles. The calorimetric profiles of blood plasma from CRC patients are found to be distinct from those of healthy individuals and those of patients with soft tissue, non-cancerous inflammation. Generally the CRC thermograms exhibit reduced heat capacity of the major albumin/globulin-assigned thermal transitions, lower enthalpy and a featureless high temperature region compared to healthy individuals. A classification of blood plasma proteome from patients with colorectal cancer (CRC1, CRC2 and CRC3 groups, and subgroups within each group CRC11–2, CRC21–2 and CRC31–2) is proposed based on the derived thermodynamic parameters. The presented data demonstrate a proof of principle and confirm that the DSC technique has a potential to monitor changes in the CRC blood plasma proteome. This study is a further step toward the validation of calorimetry as a diagnostic tool. [Display omitted] ► DSC reveals a strongly modified thermal behavior of blood plasma from CRC patients. ► The heat capacity of the major thermal transitions is altered in CRC thermograms. ► The high temperature region is featureless for majority of the CRC thermograms. ► The CRC blood plasma thermograms are classified in three groups/six subgroups. ► DSC is a sensitive tool for monitoring changes in CRC blood plasma proteome.